Cultura digital na formação inicial de pedagogos - Pontes, Evellyn Ládya Franco (2016)
This study aimed to identify the social and academic experiences in the digital culture of graduating students of the Faculty of Education, as well as recognizing its views on the creation of this culture on education. The context of this research is a private university in the city of Guarulhos, and it uses Pedagogy Degree students as subjects. It includes the analysis of quantitative and qualitative aspects to provide understanding of the phenomena with collected data from the literature review, in order to interpret the digital culture of meanings contained in theses and dissertations on technology in teacher education published in eleven renowned universities in studies of this field between 2009 and 2014; characterization Questionnaire of the researched subjects to meet the profile, the social and academic experiences of Pedagogy students and identify whether the uses of technology provide clues that they are embedded in digital culture; Questionnaire on the conceptions about the use of digital technologies in educational practice and curriculum; and a Collective nterview in order to obtain evidence of intent to use the DICT as professionals and deepen understanding of the digital culture conceptions. The results indicate that the meanings of digital culture overlap with the technology conceptions, education and its subjects, which sometimes even under a common understanding of the concept, has different nuances on the subject because the conceptions outweigh the concepts. It was found that the subjects are in a process of insertion in digital culture. They recognize the constitution of digital culture in their everyday lives, glimpse pedagogical potential in this context and intention to use the technologies. However, they do not seem to feel like subjects of an educational practice with contribution of DICT. Such situation indicates that the course does not provide opportunities for educators training in digital culture. Building the digital culture in the context of initial training in pedagogy leads us to think of the formation of competent professionals capable of mediating and encouraging the use of copyright and communication network resources, in order to form free subjects, who, in their freedom, responsibility and autonomy, can be citizens in favor of the formation of a democratic and equitable society